The stars in sixteenth-century nautical literature: A comparative study - Bénard, Inês (Proceedings of the Seminar for Arabian Studies, 2022)
The beginning of the sixteenth century was a period of intensive knowledge circulation between Atlantic and Indian Ocean navigational practices. Mariners began to incorporate new information from the disciplines of geography and astronomy into their sailing methods. Portuguese nautical instructions written in the decades after Vasco da Gama rounded the Cape of Good Hope in 1497 provide clear testimonies to this shift. This article is an attempt to characterize part of the information that circulated in this transitional period through a comparative examination of Portuguese nautical instructions and Arabic navigational treatises, focusing specifically on the stars used for latitude measurements.